Consumer Satisfaction Analysis of Product Quality and Service at Afifa Holat Restaurant in Rantau Prapat City - Siantara, Dewa Putu; Harahap, Mailina; Hasibuan, Agung Yogi Pangestu (Economic: Journal Economic and Business, 2022)
This research was conducted at the Holat Afifa Restaurant, Jalan SM. Raja No. 2, Rantau Prapat, which aims to determine the effect of product quality on consumer satisfaction and the effect of service quality on consumer satisfaction. Data analysis method using SEM-PLS method with SmartPls application. The results showed that the Holat Afifa Restaurant was always visited by its customers because it had good product quality and service quality even though the price offered was quite expensive. This is based on the results of the analysis which shows that product quality has a positive and significant effect on customer satisfaction by 94.2%, and service quality has a positive and significant effect on customer satisfaction by 15.1%.